Development of an Epilepsy Nursing Communication Tool: Improving the Quality of Interactions Between Nurses and Patients With Seizures. Issue 2 (April 2018) - Buelow, Janice; Miller, Wendy; Fishman, Jesse
Abstract : ABSTRACT: Background: Nurses have become increasingly involved in overseeing the management of patients with complex medical conditions, including those with epilepsy. Nurses who are not specialists in epilepsy can play a central role in providing optimal care, education, and support to their patients with epilepsy, given the proper tools.Objective: Our objective was to create a tool that can be used by nurses in the clinic setting to help facilitate discussion of topics relevant to enhancing medical care and management of patients with epilepsy. To address this need, a panel of epilepsy nursing experts used a patient-centered care approach to develop an Epilepsy Nursing Communication Tool (ENCT).Methods: An initial set of topics and questions was created based on findings from a literature review. Eight nurse experts reviewed and revised the ENCT using focus groups and discussion forums. The revised ENCT was provided to nurses who care for patients with epilepsy but had not been involved in ENCT development. Nurses were asked to rate the usability and feasibility on a 5-point scale to assess whether the tool captured important topics and was easy to use.Results: Ten nurses provided usability and feasibility assessments. Results indicated strong tool utility, with median scores of 4.5, 4, and 4 for usefulness, ease of use, and acceptability, respectively.Conclusions: The preliminary ENCT shows promise in providing a tool that nurses can use in their interactions with patients with epilepsy to help address the complexity of disease management, which may help improve overall patient care.